Exegesis on the dignity of the person: Bioethical implications of supernumerary embryos in in vitro fertilization - Momodu-Moka, Hassan (2025)
The purpose of this study is to analyze and present an exegesis of the concept of human dignity. This is regarding the bioethical implications surrounding supernumerary embryos. Thus, the study will be conducted from the perspective of the anthropological-personalist model. This approach places the human being at the center of its focus, distancing itself from reductionist frameworks such as radical liberalism, utilitarianism, among others, which tend to objectify human life. Consequently, this academic proposal emphasizes a fundamental moral value: human dignity, understood as an intrinsic, inherent, and immutable attribute of every human being, which must guide all scientific and technical practices. This ethical reflection seeks to highlight the importance of establishing clear bioethical boundaries in biotechnological applications. Considering that these do not affect objects but rather subjects. Therefore, through this literature review, employing a methodology based on scientific evidence (MBSE), the aim is to strengthen the moral-scientific debate, grounded in respect for human life. As well as, in the recognition of dignity as the cornerstone of research standards or in healthcare professional-patient relationship, thereby contributing to the humanization of the latter.